Analysis of The Effect of Workload, Role Conflict, Work Stress on Exit Intentions and Work Burnout - Arwansa Wahana; Iwan Kresna Setiadi; Sri Mulyantini (Politeknik Siber Cerdika Internasional, 2024)
The banking sector, including Bank Syariah X, faces challenges with high employee turnover rates, which can be attributed to factors such as workload, role conflict, and work stress. This quantitative study aims to analyze the impact of workload, role conflict, and work stress on turnover intentions and work fatigue among Bank Syariah X employees in the Jabodetabek area. A sample of 75 organic employees was selected using simple random sampling, and data were collected through questionnaire surveys. Analysis was conducted using Partial Least Square (PLS) analysis. The findings reveal that workload and role conflict significantly contribute to work stress, which in turn influences turnover intentions and job burnout. The study underscores the importance of addressing these factors to mitigate turnover and enhance employee well-being. The results provide valuable insights for academia to enrich research literature, researchers to contribute to knowledge development, and Bank Syariah X management to formulate effective policies and practices for workforce management.